2020
DOI: 10.1101/2020.11.24.392498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput characterization of photocrosslinker-bearing ion channel variants to map residues critical for function and pharmacology

Abstract: Incorporation of non-canonical amino acids (ncAAs) can endow proteins with novel functionalities, such as crosslinking or fluorescence. In ion channels, the function of these variants can be studied with great precision using standard electrophysiology, but this approach is typically labor intensive and low throughput. Here, we establish a high-throughput protocol to conduct functional and pharmacological investigations of ncAA-containing hASIC1a (human acid-sensing ion channel 1a) variants in transiently tran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 90 publications
5
6
0
Order By: Relevance
“…These experiments indicate that PcTx1 interacts with F350L* and introduces conformational changes, despite the lack of functional consequences at these concentrations. This is in line with earlier results that suggested PcTx1 to still bind to F352L hASIC1a, as pre-incubation with PcTx1 prevented the modulatory effects of BigDyn and PcTx1 could still be crosslinked with the mutant channel (Braun, Friis et al 2021). Similarly, experiments from ASIC1a/2a concatemers of different subunit stoichiometries suggested that PcTx1 also binds to ASIC1a-2a interfaces (Joeres, Augustinowski et al 2016), despite the fact that ASIC2a subunits contain a leucine at the position corresponding to 350 in mASIC1a.…”
Section: The F350l Mutation Destabilizes a Pctx1-induced Conformation...supporting
confidence: 90%
“…These experiments indicate that PcTx1 interacts with F350L* and introduces conformational changes, despite the lack of functional consequences at these concentrations. This is in line with earlier results that suggested PcTx1 to still bind to F352L hASIC1a, as pre-incubation with PcTx1 prevented the modulatory effects of BigDyn and PcTx1 could still be crosslinked with the mutant channel (Braun, Friis et al 2021). Similarly, experiments from ASIC1a/2a concatemers of different subunit stoichiometries suggested that PcTx1 also binds to ASIC1a-2a interfaces (Joeres, Augustinowski et al 2016), despite the fact that ASIC2a subunits contain a leucine at the position corresponding to 350 in mASIC1a.…”
Section: The F350l Mutation Destabilizes a Pctx1-induced Conformation...supporting
confidence: 90%
“…These experiments indicate that PcTx1 interacts with F350L* and introduces conformational changes, despite the lack of functional consequences at these concentrations. This is in line with earlier results that suggested for PcTx1 to still bind to F352L hASIC1a, as pre-incubation with PcTx1 prevented the modulatory effects of BigDyn and PcTx1 could still be crosslinked with the mutant channel (Braun, Friis et al 2021). Similarly, experiments from ASIC1a/2a concatemers of different subunit stoichiometries suggested that PcTx1 also binds to ASIC1a-2a interfaces (Joeres, Augustinowski et al 2016), despite the fact that ASIC2a subunits contain a Leu at the position corresponding to 350 in mASIC1a.…”
Section: The F350l Mutation Destabilizes a Pctx1-induced Conformational Statessupporting
confidence: 91%
“…One 12-well dish contained ECSs with resting pH (7.4), and another dish contained ECSs with activating pH (pH 6). ECSs were applied using a liquid stacking approach as described elsewhere ( Braun et al, 2021 Preprint ). The pipette tips were loaded with 25 µl pH 7.4 solution followed by 15 μl pH 6.0 solution.…”
Section: Methodsmentioning
confidence: 99%